Manajemen Pembiayaan Pendidikan Islam di Sekolah Tinggi Ilmu Tarbiyah Babussalam Aceh Tenggara - Nuriza Acela; Erawadi Erawadi; Zainal Efendi Hasibuan (Journal on Education, 2023)
Sekolah Tinggi Ilmu Tarbiyah Babussalam (STIT-BA) is a private university located in Kutacane, Southeast Aceh. In their efforts to increase the equality and quality of education, the government, society and the private sector should join hands. Different from the education system in developed countries, the education system in developing countries uses various favorable financing models for education development and prioritizes its regional budget for education development. This study uses a qualitative approach. This was done to reveal descriptive data about the actions, feelings, and experiences of the informants to the research focus. This study describes the education financing system at STIT-BA Aceh Tenggara. The results of the study show that STIT-BA uses a Centralized Financial System (SKT) for funds originating from Development Money and student tuition fees. Thus, the term "deficit" does not apply at STIT-BA. Funds allocated for certain activities, such as PPL costs, payroll and procurement of goods and other necessities. At STIT Babussalam Kutacane, the high school treasurer himself is responsible for comprehensive, proposal seminars, thesis guidance, munaqasyah, and graduation, and is responsible to the STITBA leadership. Thus, the fundraising model was implemented.